Avaliação fisiológica de sementes de Stylosanthes spp. armazenadas no BGF-UEFS - Silva, Aritana Alves da (2021)
The Semiarid region of Brazil presents a diversity of germplasm with forage potential. Among them, the genus Stylosanthes (legume forage) is native to this region and has superior characteristics for forage purposes. Although, there are already breeding programs for Stylosanthes species for the Brazilian Cerrados that have started to release cultivars, such as Estilosantes Campo Grande and BRS Bela cultivar, in the Brazilian Semiarid the studies are still punctual, but they already present important results. Studies started in 2007 with collection expeditions to collect germplasm in Bahia gave rise to the Forage Germplasm Bank of the State University of Feira de Santana (BGF-UEFS), which currently conserves 355 accessions whose physiological characterization of the seeds has not yet was carried out as recommended by the International Rules for the Conservation of Germplasm ex situ in the form of seeds. In the BGF-UEFS, the protocols for processing and separating seed lots have made it difficult to manage the germplasm, and some seeds from multiplication are lost, due to the difficulty and feasibility of efficient and fast work to conserve the multiplied material on field. For this purpose, this project sought to carry out a baseline study, in order to provide information that helps to solve the problems described and facilitate the management of the BGF-UEFS, by optimizing the different stages of the study of plant genetic resources. Thus, the aim of this work was to monitor the physiological quality of seeds stored in the medium term, verify the maintenance of physical dormancy of seeds and validate the efficiency of the already used seed conservation methodology and evaluate the viability and vigor of a sample of seeds from accessions stored in the short term, seeking to adapt the protocol for processing seeds destined for conservation. To meet the objectives, in seeds stored in the medium term, the germination test was carried out in 11 accessions of Stylosanthes from BGF-UEFS and in the seeds stored in the short term, the germination test and emergence test in five accessions. It was observed that most accessions stored in the medium term managed to maintain the physiological quality of the seeds, demonstrating that the methodology used for storage is efficient and that the storage time was not enough to overcome the seed tegumentary dormancy. In the tests carried out with seeds stored in the short term, it was observed that there is no change in the physiological quality of the seeds when they are stored inside the fruits, allowing the adaptation of the processing protocol. Thus, it can be affirmed that the storage of seeds in waterproof hermetic flasks with moisture indicator (silica gel) and placed in an uncontrolled laboratory environment is efficient for the conservation of Stylosanthes seeds in the medium term and the maintenance of the seeds within the fruit, will provide a reduction in time and labor in the storage stage, thus suggesting an adjustment in the conservation methodology in use in the BGF-UEFS.